SEXUAL OBJECTIFICATION TOWARDS SAYURI IN GOLDEN’S MEMOIRS OF GEISHA NOVEL: FEMINIST APPROACH - Afsary, Vita; Putra, Emil Eka (LPPM Universitas Putera Batam, 2020)
This research discusses reflected objectification experienced by women. The aim of the research is to describe the form sexual objectification found in Memoirs of Geisha. In this research, the researcher use objectification theory of Fredrickson & Robert and supported by several features stated by Nussbaum. The researcher uses the qualitative research with descriptive method. The researcher obtained data from reading Memoirs of a Geisha novel which was published in 1997, then highlighting data, and writes down the data found. The result of this research is that Sayuri as a main character has experienced all forms of sexual objectification with different treatment. There are seven forms of sexual objectification such as instrumentality, denial of autonomy, inertness, fungibility, ownership and denial of subjectivity.